Warehouse design: A structured approach. - Baker, Peter; Canessa, Marco (Elsevier, 2009)
In spite of the importance of warehousing to the customer service and cost levels of many businesses, there is currently not a comprehensive systematic method for designing warehouses. In this paper, the current literature on the overall methodology of warehouse design is explored, together with the literature on tools and techniques used for specific areas of analysis. The general results from the literature have then been validated and refined with reference to warehouse design companies. The output is a general framework of steps, with specific tools and techniques that can be used for each step. This is intended to be of value to practitioners and to assist further research into the development of a more comprehensive methodology for warehouse design.
Keywords: Facilities planning and design; Decision support models; Logistics; Warehouse design